2021
DOI: 10.1021/acs.jafc.1c00452
|View full text |Cite
|
Sign up to set email alerts
|

Peptides in Brewed Wines: Formation, Structure, and Function

Abstract: The traditional low-alcoholic beverages, such as grape wine, sake, and rice wine, have been consumed all over the world for thousands of years, each with their unique methods of production that have been practiced for centuries. Moderate consumption of wine is generally touted as beneficial for health, although there is ongoing debate for the responsible components in wine. In this review, the structural and functional characteristics, the formation mechanisms, and their health-promoting activities of peptides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 116 publications
0
22
0
Order By: Relevance
“…This is not the first time that N-containing compounds and especially small peptides have been found to be responsible for the quality differences in wines [20]. In addition, peptides in fermented foods are taste-active (some are also bioactive) compounds [29][30][31], promoting healthy effects and being highly susceptible to modifications during food processing due to the presence of exposed active groups in their amino acidic residues [32]. In wine they are tentatively associated to certain sensorial attributes, such as sweetness [33], bitterness, and sourness, and γ-glutamyl peptides contribute to the umami taste in fermented foods [31,33,34].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This is not the first time that N-containing compounds and especially small peptides have been found to be responsible for the quality differences in wines [20]. In addition, peptides in fermented foods are taste-active (some are also bioactive) compounds [29][30][31], promoting healthy effects and being highly susceptible to modifications during food processing due to the presence of exposed active groups in their amino acidic residues [32]. In wine they are tentatively associated to certain sensorial attributes, such as sweetness [33], bitterness, and sourness, and γ-glutamyl peptides contribute to the umami taste in fermented foods [31,33,34].…”
Section: Discussionmentioning
confidence: 94%
“…In addition, peptides in fermented foods are taste-active (some are also bioactive) compounds [29][30][31], promoting healthy effects and being highly susceptible to modifications during food processing due to the presence of exposed active groups in their amino acidic residues [32]. In wine they are tentatively associated to certain sensorial attributes, such as sweetness [33], bitterness, and sourness, and γ-glutamyl peptides contribute to the umami taste in fermented foods [31,33,34]. More recently, dipeptides have been reported to contribute to the perceived quality of commercial Pinot noir [20] and Nand S-containing compounds similarly contribute to Chardonnay wines [35].…”
Section: Discussionmentioning
confidence: 99%
“…Fermented alcoholic beverages are the typical fermented food in the world, and currently there is ongoing debate about the health-promoting benefit of drinking these beverages. However, it was revealed that some un-alcohol substances in the beverages could bring beneficial effects to human, such as BAP [72]. It has been reported that two pyroglutamyl peptides (pyroGlu-Tyr and pyroGlu-Asn-Ile) with anti-colitic activity had been identified from the traditional Japanese alcoholic beverage, sake.…”
Section: Winementioning
confidence: 99%
“…It is primarily brewed with glutinous rice as raw material, wheat Qu, and yeast (such as Saccharomyces cerevisiae ) as saccharifying agents and starter. Wheat Qu contained complex microflora, comprising Aspergillus spp., Rhizopus spp., Fusarium , Mucor , Saccharopolyspora , lactic acid bacteria, and yeasts secrete a diversity of enzymes, primarily liquefying enzyme, saccharifying enzyme, proteolytic enzyme, peptidase, lipase, and esterase [ 25 ]. During the process of wheat Qu production, pre-fermentation, and post-fermentation, numerous metabolic enzymes formed by microorganisms promote the transformation of high molecular substances (for example, starch and proteins) in glutinous rice and wheat into polysaccharides, oligosaccharides, ethanol, peptides, and amino acids, and result in the generation of polyphenol, organic acids, and flavor substances [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%